Priming-Dependent Modulation of Secretome in Placenta- and Adipose-Derived Mesenchymal Stromal/Stem Cells: Toward Cell-Free Immunoregenerative Therapies for Osteochondral and Degenerative Joint Diseases - Mattia Emanuela Ligotti; Elisabetta Scalia; Simone Dario Scilabra; Margot Lo Pinto; Alessia Gallo; Roberta Vazzana; Nicola Cuscino; Oriana Lo Re; Clara Pipia; Giandomenico Amico; Silvia Lopa; Alessandra Colombini; et al. (Stem Cell Reviews and Reports, 2026)

Machine learning supported olive oil compound profiling for assessing geographic and cultivar authenticity - Gaia Meoni; Chiara Vita; Leonardo Tenori; Lorenzo Venturini; Miriam Ascolese; Alissa Mattei; Lucia Tacconi; Maria Teresa Ceccherini; Claudio Luchinat; Simone Tommasini; Sandro Moretti; Samuel Pelacani (Food Research International, 2026)

Food Safety and quality of some Italian honey: Study of long-persistent contaminants (heavy metals and PFAS) in different production areas in southern Italy - Sergio Passarella; Simone Moretti; Alessia Iannone; Fabiana Carriera; Sonia Ganassi; Dalila Di Criscio; Loretta De Giorgi; Giulia Corazzi; Ivan Notardonato; Carolina Barola; Roberta Galarini; Pasquale Avino; et al. (Food Chemistry, 2026)

Determination of ten emerging poly- and perfluoroether carboxilates and sulfonates in food: Method development and validation - Carolina Barola; Elisabetta Bucaletti; Danilo Giusepponi; Simone Moretti; Tamara Tavoloni; Roberta Galarini (Food Chemistry, 2025)

Geochemical fingerprinting of extra virgin olive oils based on radiogenic strontium isotopes - Samuel Pelacani; Simone Tommasini; Mattia Ferrari; Matthias Ghiotto; Elena Pecchioni; Roberto Riccio; Sandro Moretti (Science of The Total Environment, 2025)

Corrigendum to “Target determination and suspect screening of legacy and emerging per-and poly-fluoro poly-ethers in wild boar liver, in Italy” [Chemosphere 312 (2023) 137214] - Simone Moretti; Carolina Barola; Danilo Giusepponi; Fabiola Paoletti; Arianna Piersanti; Olga Tcheremenskaia; Gianfranco Brambilla; Roberta Galarini (Chemosphere, 2024)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Flood plain inundation modeling with explicit description of land surface macrostructures - Simone Pizzileo; Giovanni Moretti; Stefano Orlandini (Advances in Water Resources, 2024)

Assessment of the combined inputs of antimicrobials from top soil improvers and irrigation waters on green leafy vegetable fields - Carolina Barola; Gianfranco Brambilla; Roberta Galarini; Simone Moretti; Stefano Morabito (Food Additives & Contaminants: Part A, 2024)

Occurrence and pattern of legacy and emerging per- and Poly-FluoroAlkyl substances (PFAS) in eggs of loggerhead turtle Caretta caretta from western Mediterranean - Simone Moretti; Gianfranco Brambilla; Fulvio Maffucci; Carolina Barola; Elisabetta Bucaletti; Sandra Hochscheid; Silvia Canzanella; Roberta Galarini; Mauro Esposito (Environmental Pollution, 2024)

Spatial mismatch between wild bee diversity hotspots and protected areas - Joan Casanelles‐Abella; Simone Fontana; Eliane Meier; Marco Moretti; Betrand Fournier (Conservation Biology, 2023)
Wild bees are critical for multiple ecosystem functions but are currently threatened. Understanding the determinants of the spatial distribution of wild bee diversity is a major research gap for their conservation. We modeled wild bee α and β taxonomic and functional diversity in Switzerland to uncover countrywide diversity patterns and determine the extent to which they provide complementary information, assess the importance of the different drivers structuring wild bee diversity, identify hotspots of wild bee diversity, and determine the overlap between diversity hotspots and the network of protected areas. We used site‐level occurrence and trait data from 547 wild bee species across 3343 plots and calculated community attributes, including taxonomic diversity metrics, community mean trait values, and functional diversity metrics. We modeled their distribution with predictors describing gradients of climate, resource availability (vegetation), and anthropogenic influence (i.e., land‐use types and beekeeping intensity). Wild bee diversity changed along gradients of climate and resource availability; high‐elevation areas had lower functional and taxonomic α diversity, and xeric areas harbored more diverse bee communities. Functional and taxonomic β diversities diverged from this pattern, with high elevations hosting unique species and trait combinations. The proportion of diversity hotspots included in protected areas depended on the biodiversity facet, but most diversity hotspots occurred in unprotected land. Climate and resource availability gradients drove spatial patterns of wild bee diversity, resulting in lower overall diversity at higher elevations, but simultaneously greater taxonomic and functional uniqueness. This spatial mismatch among distinct biodiversity facets and the degree of overlap with protected areas is a challenge to wild bee conservation, especially in the face of global change, and calls for better integrating unprotected land. The application of spatial predictive models represents a valuable tool to aid the future development of protected areas and achieve wild bee conservation goals.

Target determination and suspect screening of legacy and emerging per- and poly-fluoro poly-ethers in wild boar liver, in Italy - Simone Moretti; Carolina Barola; Danilo Giusepponi; Fabiola Paoletti; Arianna Piersanti; Olga Tcheremenskaia; Gianfranco Brambilla; Roberta Galarini (Chemosphere, 2023)

Effects of the Application of Decellularized Amniotic Membrane Solubilized with Hyaluronic Acid on Wound Healing - Maria Eduarda Anastácio Borges Corrêa; Carolini Mendes; João Vitor Silvano Bittencourt; Aline Takejima; Isio Carvalho de Souza; Simone Cristina Dizaró de Carvalho; Ingrid Gabriela Orlandini; Thiago Antonio Moretti de Andrade; Luiz César Guarita-Souza; Paulo Cesar Lock Silveira (Annals of Biomedical Engineering, 2022)

Reconciling trait based perspectives along a trait‐integration continuum - Simone Fontana; Sergio Rasmann; Francesco de Bello; Francesco Pomati; Marco Moretti (Ecology, 2021)
Trait based ecology has developed fast in the last decades, aiming to both explain mechanisms of community assembly, and predict patterns in nature, such as the effects of biodiversity shifts on key ecosystem processes. This body of work has stimulated the development of several conceptual frameworks and analytical methods, as well as the production of trait databases covering a growing number of taxa and organizational levels (from individuals to guilds). However, this breeding ground of novel concepts and tools currently lacks a general and coherent framework, under which functional traits can help ecologists organize their research aims, and serve as the common currency to unify several scientific disciplines. Specifically, we see a need to bridge the gaps between community ecology, ecosystem ecology, and evolutionary biology, in order to address the most pressing environmental issues of our time. To achieve this integration goal, we define a trait‐integration continuum, which reconciles alternative trait definitions and approaches in ecology. This continuum outlines a coherent progression of biological scales, along which traits interact and hierarchically integrate from genetic information, to whole organism fitness‐related traits, to trait syndromes and functional groups. Our conceptual scheme proposes that lower‐level trait integration is closer to the inference of ecoevolutionary mechanisms determining population and community properties, whereas higher‐level trait integration is most suited to the prediction of ecosystem processes. Within these two extremes, trait integration varies on a continuous scale, which relates directly to the inductive‐deductive loop that should characterize the scientific method. With our proposed framework, we aim to facilitate scientists in contextualising their research based on the trait‐integration levels that matter most to their specific goals. Explicitly acknowledging the existence of a trait‐integration continuum is a promising way for framing the appropriate questions, thus obtaining reliable answers and results that are comparable across studies and disciplines.

Multiclass methods for the analysis of antibiotic residues in milk by liquid chromatography coupled to mass spectrometry: A review - Rosanna Rossi; Giorgio Saluti; Simone Moretti; Irene Diamanti; Danilo Giusepponi; Roberta Galarini (Food Additives & Contaminants: Part A, 2018)

Determination of macrocyclic lactones in food and feed - Roberta Galarini; Giorgio Saluti; Simone Moretti; Danilo Giusepponi; Guglielmo Dusi (Food Additives & Contaminants: Part A, 2013)